2022
DOI: 10.1001/jamainternmed.2022.1657
|View full text |Cite|
|
Sign up to set email alerts
|

Time to Clinical Benefit of Intensive Blood Pressure Lowering in Patients 60 Years and Older With Hypertension

Abstract: This secondary analysis of randomized clinical trials estimates the time needed to potentially derive clinical benefit from intensive blood pressure treatment in patients 60 years and older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…The SPRINT and SPRINT-based cost-effectiveness analyses have provided clinical benefits and good cost-effectiveness. 4 , 5 , 6 , 12 , 14 Nevertheless, the concerns of an intensive target in older patients (SBP <120 mm Hg) may lead to inconsistent SBP targets (ie, 150 mm Hg for the American College of Physicians–American Academy of Family Physicians, 140 mm Hg for the Chinese Geriatrics Society, 130 to 139 mm Hg for the European guidelines, <130 mm Hg for the AHA-ACC guidelines). 7 , 8 , 9 , 10 Compared with SPRINT, despite lacking mortality reduction, less intensive blood pressure control (mean, 130 mm Hg in the STEP trial) for older patients still reduces cardiovascular incidence and showed cost-effective advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPRINT and SPRINT-based cost-effectiveness analyses have provided clinical benefits and good cost-effectiveness. 4 , 5 , 6 , 12 , 14 Nevertheless, the concerns of an intensive target in older patients (SBP <120 mm Hg) may lead to inconsistent SBP targets (ie, 150 mm Hg for the American College of Physicians–American Academy of Family Physicians, 140 mm Hg for the Chinese Geriatrics Society, 130 to 139 mm Hg for the European guidelines, <130 mm Hg for the AHA-ACC guidelines). 7 , 8 , 9 , 10 Compared with SPRINT, despite lacking mortality reduction, less intensive blood pressure control (mean, 130 mm Hg in the STEP trial) for older patients still reduces cardiovascular incidence and showed cost-effective advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a shorter duration of antihypertensive use, higher mortality as a competing risk for CVD, and adherence may influence the health-economic incentive. 12 , 13 Therefore, this study aimed to estimate the lifetime direct medical costs and quality-adjusted life-years (QALYs) of intensive and standard SBP treatments among the older population with hypertension in different countries to examine the cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 63 A recent meta-analysis of six randomised clinical trials including 27,400 hypertensive patients (aged ≥60) found that intensive systolic blood pressure lowering (systolic BP < 140 mm Hg) reduced the incidence of major adverse cardiovascular events by 21%. 64 …”
Section: Pharmacotherapymentioning
confidence: 99%
“…An analysis of six trials (original data from two trials and reconstructed data from four trials) that included 27,414 participants demonstrated that intensive BP treatment with a systolic BP target <140 mmHg was significantly associated with a 21% reduction in MACE (HR 0.79; 95% CI [0.71–0.88]; p<0.001). [ 10 ] On average, 9.1 months were needed to prevent one MACE per 500 patients with the intensive BP treatment; in contrast, 19.1 and 34.4 months were estimated to avoid one MACE per 200 and 100 patients with standard treatment, respectively.…”
Section: Intensive Blood Pressure Controlmentioning
confidence: 99%